Airline network planning and scheduling - Abdelghany, Ahmed F.; Abdelghany, Khaled (Wiley series in operations research and management science, 2019)
A concise resource to the best practices and problem-solving ideas for understanding the airline network planning and scheduling process Airline Network Planning and Scheduling offers a comprehensive resource that is filled with the industry's best practices that can help to inform decision-modeling and the problem-solving process. Written by two industry experts, the book is designed to be an accessible guide that contains information for addressing complex challenges, problems, and approaches that arise on the job. The chapters begin by addressing the complex topics at a broad, conceptual level before moving on to more detailed modeling in later chapters. This approach follows the standard airline planning process and reflects the duties of the day-to-day job of network/schedule planners. To help gain a practical understanding of the information presented, each chapter includes exercises and data based on real-world case studies. In addition, throughout the book there are graphs and illustrations as well as, information on the most recent advances in airline network and planning research. This important resource: • Takes a practical approach when detailing airline network planning and scheduling practices as opposed to a theoretical perspective • Puts the focus on the complexity and main challenges as well as current practices and approaches to problem-solving and decision-making • Presents the information in a logical sequence that begins with broad, conceptual topics and gradually delves into more advanced topics that address modeling • Contains international standard airline planning processes, the day-to-day responsibilities of the job, and outlines the steps taken when building an airline network and schedule • Includes numerous case studies, exercises, graphs, and illustrations throughout Written for professionals and academics, Airline Network Planning and Scheduling offers a resource for understanding best practices and models as well as the challenges involved with network planning and scheduling. Ahmed Abdelghany, PhD , is Professor in the Department of Management, Marketing, and Operations at Embry-Riddle Aeronautical University. His past experience includes being a senior analyst in the Information Services Division (ISD) at United Airlines. Khaled Abdelghany, PhD , is Professor and former Chair in the Department of Civil and Environmental Engineering at the Southern Methodist University. He has worked as an analys...